Fracture toughness of old bridge steel - Mytych-Kumańska, Eliza; Kossakowski, Paweł (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
The subject of paper is related to problems the of fracture toughness of old steel bridge which was taken from the railway bridge, that was loaded during more than 100 years. The basic problems of fracture mechanics, as well as detailed information on the procedures of determination of material fracture toughness, which were used in the steel bridge research, are presented. The results of the study, the critical values of JQ integral, defining the fracture toughness of investigated steel are discussed.